Influence of formulation on the oxidative stability of water-in-oil emulsions. (1st July 2016) - Dridi, Wafa; Essafi, Wafa; Gargouri, Mohamed; Leal-Calderon, Fernando; Cansell, Maud
Highlights: The impact of water-in-oil emulsion formulation on lipid oxidation was studied. The interfacial composition influenced lipid oxidation. The encapsulation of iron within the droplets accelerated the oxidation process. Chelated iron catalyzed oxidation to a lesser extent than free iron ions. Irrespectively of the dispersed phase composition, emulsions based on polyunsaturated oils were prone to oxidation. Abstract: The oxidation of water-in-oil (W/O) emulsions was investigated, emphasizing the impact of compositional parameters. The emulsions had approximately the same average droplet size and did not show any physical destabilization throughout the study. In the absence of pro-oxidant ions in the aqueous phase, lipid oxidation of the W/O emulsions was moderate at 60 °C and was in the same range as that measured for the neat oils. Oxidation was significantly promoted by iron encapsulation in the aqueous phase, even at 25 °C. However, iron chelation reduced the oxidation rate. Emulsions based on triglycerides rich in polyunsaturated fatty acids were more prone to oxidation, whether the aqueous phase encapsulated iron or not. The emulsions were stabilized by high- and low-molecular weight surfactants. Increased relative fractions of high molecular weight components reduced the oxidation rate when iron was present.